Wound healing properties of a chimeric form of human GM-CSF in a rat burn injury model - M. B. Pykhtina; S. M. Miroshnichenko; M. A. Karpov; A. A. Abyshev; K. I. Mosalev; M. V. Kotova; A. A. Beklemishev; R. A. Knyazev (Сибирский научный медицинский журнал)
Thermal burns are one of the common types of human injuries, causing in severe cases an extensive immune response both locally in the wound and having a systemic effect. The search for new means of local treatment of burn wounds remains an urgent task. The aim of this study was to investigate the wound healing properties of recombinant granulocyte-macrophage colony-stimulating factor (ryGM-CSF) and its prolonged chimeric form with human apolipoprotein AI (ryGM-CSF-apoAI) on the model of burn injury in rats. Material and methods. ryGM-CSF and ryGM-CSF-apoAI obtained by expression in yeast P. pastoris were used in this work. The study was performed on 27 Wistar rats, which were modeled burns of III degree. The wound-healing effect of recombinant cytokines was evaluated morphologically, and the expression of cytokine genes - markers of the course of the wound process and angiogenesis - was measured. Results and discussion. ryGM-CSF is known to accelerate wound healing. Human rGM-CSF on the rat burn model showed both the properties of a cytokine influencing angiogenesis, increasing the number of vessels, and being a foreign protein stimulated the immune response, increasing prolonged the number of lymphocytes and supporting inflammation. The chimeric form of cytokine ryGM-CSF-apoAI reduced inflammation, accelerated the change of wound healing phases and, as a consequence, reduced the number of neutrophils by 16 days. Unexpectedly, it induced maturation of vessels, which in this case had normal lumen, size, and were lined with endothelium. The ratio Angpt1 and Angpt2 gene mRNA content was 2-fold higher when ryGM-CSF-apoAI was used, compared to control and ryGM-CSF administration. Conclusions. With xenogeneous administration, recombinant human GM-CSF prolongs inflammation due to early lymphocytic response to foreign protein and increased neutrophil content at later wound healing periods. The chimeric form ryGM-CSF-apoAI reduces cytokine immunogenicity by promoting earlier replacement of neutrophils by macrophages and fibroblasts and stimulates maturation of high-grade blood vessels.